Measurement and detection of voltage dips and swells in power circuits - Shanmugasundaram, N; Vajubunnisa Begum, R; N. Ganesh, E (International Journal of Engineering and Technology, 2018)
The different power quality phenomena may have characteristics quite different from each other in terms of amplitude, duration, repetition, effects on the system elements, perception of users, etc. Events like interruptions and voltage dips and swells are characterized as phenomena where the root mean square (rms) value of the supply voltage falls below or rises above a prefixed threshold. Description of three-phase measurement device for detecting voltage dips and swells in electric power network is given in this paper. The device has been tested on a real electric power network and practical results of measurement are given.